Nurses’ Perspectives on the Sleep Quality of Hospitalized Patients in Al Ahsa, Saudi Arabia - Rabie Adel El Arab; Husam Alzghoul; Mohammad S. Abu-Mahfouz; Zainab Aldarwish; Mariam Abbadi; Eman Ghashi; Ghasaq Alsaffar; Wujd Alasmkh; Mohamed Mahmoud Seweid (Nursing Reports)
Background: Sleep quality is crucial for patient recovery and well-being, yet hospitalized patients often suffer from poor sleep due to environmental disruptions, clinical routines, and psychosocial stressors. While these challenges are well-documented, qualitative insights into nurses’ perspectives—essential frontline providers shaping the sleep environment—are scarce, especially within rapidly evolving healthcare systems like Saudi Arabia’s. This study explores nurses’ perceptions of factors influencing patient sleep quality in a private hospital in Al Ahsa, Saudi Arabia, and identifies strategies for improvement. Methods: We conducted a qualitative, cross-sectional study using semi-structured interviews with 14 registered nurses from diverse nationalities, specialties (Obstetrics/Gynecology, Medical-Surgical, Pediatrics, Intensive Care, Orthopedics, Bariatrics), and experience levels. Interviews were conducted in Arabic or English, audio-recorded, transcribed, and thematically analyzed using ATLAS.ti software. Roy’s Adaptation Model guided the examination of environmental, patient-specific, and systemic factors affecting sleep. Findings: Four primary themes emerged: (1). Environmental Factors: noise from alarms, equipment, family presence, and late-night activities, along with abrupt lighting changes, consistently disrupted sleep. (2). Patient-Specific Factors: pain, emotional distress, cultural expectations, and family involvement influenced sleep experiences. (3). Systemic and Contextual Factors: language barriers, infrastructural disparities between private and governmental hospitals, and limited resources can impeded effective sleep-promoting strategies. (4). Role of Health Technology: nurses recognized the potential of innovations like smart lighting and wearable monitors to enhance sleep quality but faced challenges in implementation due to knowledge gaps and limited familiarity. Roy’s Adaptation Model highlighted how effective adaptation through physiological and cognitive–emotional pathways, as observed by nurses, was facilitated or hindered by these factors. Conclusions: Enhancing in-hospital sleep quality requires a holistic, culturally sensitive approach that integrates environmental modifications, patient-centered care, and systemic improvements. Strategic investments in staff communication training, infrastructural upgrades, language support services, and the adoption of health technologies can promote adaptive responses and optimize patient rest. By leveraging theory-driven insights and context-specific strategies, healthcare systems—particularly those undergoing rapid development—can better support nurses in fostering restorative sleep environments as a fundamental component of patient-centered care, thereby enhancing patient recovery, satisfaction, and overall well-being.